P235 Assessment of diaphragm motion in patients with unilateral or asymmetrical pleural effusions - Aldik, MG; Sibly, A; Telisinghe, L; Daneshvar, C (Thorax, 2017)
IntroductionThe diaphragm is the most important respiratory muscle. In patients with pleural effusions, abnormal diaphragm shape and movement on inspiration may be observed. We aimed to explore the possible significance of these findings in a our pleural service.MethodsBetween August 2015 and June 2016, all patients with an index thoracic ultrasound scan reporting a unilateral or significantly asymmetrical bilateral pleural effusion were retrospectively assessed. Patients were examined in the upright position by an RCR level 1 trained physician. A routine standardised reporting form was used to record dimensions, echogenic properties, the presence of septations, pleural nodularity and diaphragm nodularity, shape and movement. Pleural fluid characteristics and final diagnoses were assessed.ResultsOf 491 patients assessed, 259 met the inclusion criteria. Thoracocentesis was performed in 70%, with exudative defined by Light’s criteria being met in 121 (47%). A diagnosis was established in 84% of cases with the commonest aetiology being malignancy (32%). The median [interquartile range] size of the pleural effusions was 8 [5–10] cm in medial depth and 3 [2–4] rib spaces in height, with 118 (46%) being echogenic. Diaphragm assessment revealed that paradoxical movement of the diaphragm was observed in 56 (22% [95% CI 16.6%–26.6%]) of patients while 11 (4.3% [95% CI 1.8%–6.7%]) had an inverted diaphragm. Patients with paradoxical diaphragm movement had larger effusions (median depth 11 cm versus 7 cm; p<0.001) and a higher proportion of effusions of malignant aetiology (45% versus 11%; p<0.001) when compared with individuals with normal diaphragm movement. In multivariate analysis, adjusting for age, gender, effusion depth and height and diaphragm shape, effusions of malignant aetiology were associated with an increased odds of paradoxical diaphragm movement (adjusted odds ratio 4.47 (95% CI 1.83–10.95; p<0.001).ConclusionParadoxical diaphragm movement in the context of a unilateral or asymmetrical pleural effusion is frequently observed, is independently associated with malignant pleural effusions and may be a useful point of care clinical sign.